(untitled) (Hershey PA, 2006)
This book identifies the main areas of cognitive science and for each area, how different system designs benefit from the findings made in that area"--Provided by publisher
Keywords: Human-computer interaction,User interfaces (Computer systems),Cognition,Cognitive science,Giao diện người dùng (Hệ thống máy tính),Tác động lẫn nhau giữa máy tính và con người